1994
DOI: 10.1002/ajmg.1320530314
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation that the conotruncal anomaly face syndrome is associated with a deletion within 22q11.2

Abstract: The so-called "conotruncal anomaly face syndrome" (CTAFS) is characterized by a peculiar facial appearance associated with congenital heart disease (CHD), especially cardiac outflow tract defects such as tetralogy of Fallot (TOF), double outlet right ventricle (DORV), and truncus arteriosus (TAC). CTAFS and the DiGeorge anomaly (DGA) have many similar phenotypic characteristics, suggesting that they share a common cause. In many cases DGA is known to be associated with monosomy for a region of chromosome 22q11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(66 citation statements)
references
References 10 publications
4
61
1
Order By: Relevance
“…14 Furthermore, right aortic arch, pulmonary atresia, or absent pulmonary valve syndrome are common morphological features among TOF patients with 22q11 deletion. 16,17 This high incidence of right aortic arch (50%) and pulmonary atresia (19%) in our patients with marked aortic root dilatation and the relatively common coexistence of absent pulmonary valve syndrome may suggest a possible link between aortic root dilatation and chromosome 22 q11deletion. However, this is purely speculative and we do not have data on phenotypes or chromosomal analysis for our patients.…”
Section: Potential Factors Relating To Late Aortic Root Dilatation Inmentioning
confidence: 60%
“…14 Furthermore, right aortic arch, pulmonary atresia, or absent pulmonary valve syndrome are common morphological features among TOF patients with 22q11 deletion. 16,17 This high incidence of right aortic arch (50%) and pulmonary atresia (19%) in our patients with marked aortic root dilatation and the relatively common coexistence of absent pulmonary valve syndrome may suggest a possible link between aortic root dilatation and chromosome 22 q11deletion. However, this is purely speculative and we do not have data on phenotypes or chromosomal analysis for our patients.…”
Section: Potential Factors Relating To Late Aortic Root Dilatation Inmentioning
confidence: 60%
“…Very interesting have been recent studies demonstrating that the genes for the DiGeorge and velocardiofacial syndromes are at the same locus on chromosome 22 (e.g., Driscoll et al, 1992a,b;Weyerts and Jones, 1992). It has also been found that patients initially diagnosed as having the DiGeorge syndrome, and who survive through surgical correction, other therapy, or spontaneous resolution of their lifethreatening abnormalities, become clinically indistinguishable from patients with the velocardiofacial syndrome (Weyerts and Jones, 1992;Matsuoka et al, 1994). The velocardiofacial syndrome was originally described by Shprintzen et al (1978) as consisting of cleft palate (overt or submucous) cono-truncal cardiovascular defects and characteristic facial appearance, but no pha-ryngeal gland problems {i.e., thymus and parathyroid deficiencies).…”
Section: (C) Digeorge Syndromementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] In addition, deletion studies are now being performed routinely in the face of solitary findings such as velopharyngeal incompetence, cardiac anomalies, immunodeficiency, hypocalcemia, and learning disabilities or mental retardation. 10 -17 The 22q11.2 deletion is quite possibly one of the most common chromosomal disorders in humans.…”
mentioning
confidence: 99%